PERAN PENGGUNAAN CANVA DALAM PENERAPAN MEDIA PEMBELAJA-RAN FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMK NEGERI 14 MEDAN - Florensia Raissa Septiasi Br Simamora; Bisrul Hapis Tambunan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of using Canva in the implementation of flipbook learning media to improve vocational high school (SMK Negeri 14 Medan) students' learning outcomes. Canva is utilized as an intuitive graphic design platform that allows creative teachers to assemble interactive digital modules equipped with visuals, hyperlinks, and structured layouts. Using a qualitative descriptive approach, this research collected data through classroom observations, in-depth interviews with teachers and students, and documentation of students' academic works. The findings reveal that Canva serves a pivotal role in bridging structural learning designs into highly engaging digital flipbooks. The interactive and visual presentation of the flipbook significantly overcomes cognitive fatigue, clarifies abstract technical concepts, and fosters autonomous learning. Consequently, students' enthusiasm, active participation, and mastery of learning competencies showed notable enhancement. The study concludes that the creative integration of Canva in designing digital flipbooks serves as an effective, low-cost technological alternative to elevate instructional quality and student performance in vocational education SMK Negeri 14 Medan.